CONCEPTUAL BACKGROUND OF THE ESSENTIAL INSTITUTIONALIZATION OF A PHILOSOPHY OF THE BIOINTELLECTOSPHERE - V. Smirnov, Sergei; N. Tarasova, Aiziriak (Gênero & Direito, 2019)
Under. In this paper, the author characterizes the conceptual foundations of building the philosophy of the bio-elelectic sphere as a theoretical construct, which development will allow revealing the essential aspects of the strategy of rational socio-natural development, determining the directions for its subsequent implementation. "Biotelectectosphere (bios - life, sphaira - sphere, Latin intellectus - intellect) – the sphere of intelligent organization of life – the stage of development of the biosphere, where human activity will be aimed at preserving and maintaining the conditions necessary for the optimal existence of life – the geological factor, which is the initial prerequisite for the emergence and existence of mankind